The impact of change in exchange rate on foreign investment in China from 2005 to 2020 - Chen, Tingyu (2023)
The main objectives of this study are to determine (1) whether monthly changes in the RMB exchange rate directly affect FDI in China from 2005 to 2020, (2) whether China's FDI directly affects the exchange rate in China from 2005 to 2020, and (3) whether the Sino-US trade war has an effect on some FDI components. The period of fixed exchange rates has officially ended as of July 2005 in order to accommodate economic globalization and domestic economic growth. The RMB has continued to increase after the exchange rate deregulation. Determining whether changes in the RMB exchange rate have an effect on FDI inflows to China, if FDI inflows to China have an effect on the RMB exchange rate, and the impact of the U.S.-China trade war on the FDI component from both theoretical and practical perspectives.